2023
DOI: 10.1021/jacs.3c03631
|View full text |Cite
|
Sign up to set email alerts
|

Electrochromic Corundum-like Compound Based on the Reversible (De)insertion of Lithium: Li2Ni2W2O9

Simon Redor,
Louis Godeffroy,
Gwenaëlle Rousse
et al.

Abstract: The search for efficient anodic electrochromic materials is essential to the development of electrochromic devices, such as smart windows. Magnetron-sputtered lithium-nickeltungsten mixed oxides are good candidates to tackle this issue; however, they display a complicated microstructure, making it difficult to pinpoint the origin of their electro-optical properties. Herein, by exploring the Li 2 O−NiO−WO 3 phase diagram, we obtained a new phase, Li 2 Ni 2 W 2 O 9 , that crystallizes in the orthorhombic Pbcn sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 75 publications
(106 reference statements)
0
7
0
Order By: Relevance
“…[53] However, poor cycling stability and the limited difference in transmittance between bleached and colored states limit the applications. To solve these problems, Redor et al [51] undertook the synthesis of a novel phase named Li 2 Ni 2 W 2 O 9 (LNWO) via a solid-state reaction. This compound exhibits a layered structure characterized by the alternating arrangement of NiO 6 and WO 6 octahedra, and Li + is located in the interlayer gap.…”
Section: Inorganic Ecmsmentioning
confidence: 99%
See 2 more Smart Citations
“…[53] However, poor cycling stability and the limited difference in transmittance between bleached and colored states limit the applications. To solve these problems, Redor et al [51] undertook the synthesis of a novel phase named Li 2 Ni 2 W 2 O 9 (LNWO) via a solid-state reaction. This compound exhibits a layered structure characterized by the alternating arrangement of NiO 6 and WO 6 octahedra, and Li + is located in the interlayer gap.…”
Section: Inorganic Ecmsmentioning
confidence: 99%
“…Reprinted (adapted) with permission. [51] Copyright 2023 American Chemical Society. (g) Device structure.…”
Section: Inorganic Ecmsmentioning
confidence: 99%
See 1 more Smart Citation
“…RM is a label-free optical imaging technique that leverages local changes in the refractive index at the image interface to elucidate various (electro-)­chemical phase transformations. Garcia et al ,, demonstrated that, in the context of metal oxidation, light intensities correlated ex situ with surface analysis techniques can indicate phenomena such as dealloying, subsurface corrosion, etching, or pitting in Al alloys. Recently, optical models utilizing light interference at oxidized metal interfaces have shown that variations in optical intensities can quantitatively relate to the thickness (to nanometer precision) and composition of surface films. ,,, These parameters are central to our understanding of metal passivation and corrosion protection.…”
Section: Introductionmentioning
confidence: 99%
“…They enable deciphering at high throughput and high spatial resolution intricate chemical mechanisms. ECL imaging is indeed also used to decipher the coreactant pathways or reactivity of different micro-/nano-objects. , In particular, the (electro)­chemical mechanisms operating in bead-based ECL immunoassays have been investigated by analyzing the ECL signals. ,,,,, Mechanistic insights are most often reached by considering the modeling of the transport and chemical reactivity of the ECL reaction intermediates. However, as in other optical microscopy configurations, ,, modeling the optical wave propagation in the objects under investigation (and the optical properties of the media used) enables further mechanistic insights. In the context of ECL, considering interference effects, for example, enabled probing the coreactant intermediate stability .…”
mentioning
confidence: 99%